2009
DOI: 10.1111/j.1398-9995.2008.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan catabolites regulate mucosal sensitization to ovalbumin in respiratory airways

Abstract: Our data suggest that, in addition to their role in IFN-gamma-mediated inhibition of allergic airway inflammation, products of tryptophan catabolism play an important role in the prevention of sensitization to potential allergens in the respiratory airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Thus, intratracheal instillation of 3-HAA ameliorates experimental asthma in OVA-challenged mice by impairing the functionality of, and inducing apoptosis in, Th2 cells via inhibiting NF-κB signalling within these cells [236]. In a murine model of mucosal tolerance, although IDO1 inhibition with 1-MT attenuated OVA-induced tolerance upon OVA-sensitisation and rechallenge, treatment with a mixture of Kyn and 3-HAA restored tolerance in 1-MT-treated mice [321]. Similarly, administration of Kyn, 3-HK or xanthurenic acid reduced lung eosinophil and Th2 cytokine levels in allergic mice receiving suboptimal allergen immunotherapy [320].…”
Section: Transplantation the Ultimate Goal In Organ Transplantationmentioning
confidence: 81%
“…Thus, intratracheal instillation of 3-HAA ameliorates experimental asthma in OVA-challenged mice by impairing the functionality of, and inducing apoptosis in, Th2 cells via inhibiting NF-κB signalling within these cells [236]. In a murine model of mucosal tolerance, although IDO1 inhibition with 1-MT attenuated OVA-induced tolerance upon OVA-sensitisation and rechallenge, treatment with a mixture of Kyn and 3-HAA restored tolerance in 1-MT-treated mice [321]. Similarly, administration of Kyn, 3-HK or xanthurenic acid reduced lung eosinophil and Th2 cytokine levels in allergic mice receiving suboptimal allergen immunotherapy [320].…”
Section: Transplantation the Ultimate Goal In Organ Transplantationmentioning
confidence: 81%
“…1a), which has previously demonstrated that intraperitoneal (i.p.) injection of Alum/OVA cannot sensitize mice to allergic airway disease that have already been exposed to inhaled OVA in the absence of an adjuvant (20). In our hands, tolerized mice that underwent a subsequent sensitization regimen via i.p.…”
Section: Resultsmentioning
confidence: 99%
“…Splenocytes were isolated using Lymphocyte Separation Media (MP Biomedicals, Solon, OH) following mechanical disruption as previously described (20). 4 × 10 6 cells/ml were cultured in RPMI-1640 supplemented with 10% FBS (Cell Generation, Fort Collins, CO), penicillin/streptomycin, L-glutamine, folic acid, and 2-ME and treated with 100 μg/ml OVA.…”
Section: Methodsmentioning
confidence: 99%
“…In one study, the mouse model used involved intranasal inoculation of lipopolysaccharide-free ovalbumin with subsequent tests for tolerance by intraperitoneal sensitization and intranasal re-challenge [57]. In the same model, another study reported that 1MT could partly reverse the suppressive effects of immunotherapy on airway eosinophilia and Th2 cytokine levels.…”
Section: Ido In Allergic Airway Disease and Asthmamentioning
confidence: 99%